Discover answers to your most pressing questions at Westonci.ca, the ultimate Q&A platform that connects you with expert solutions. Join our platform to connect with experts ready to provide detailed answers to your questions in various areas. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
Answer:
x = - 2
Step-by-step explanation:
Given
[tex]2^{x+3}[/tex] × [tex]3^{x+4}[/tex] = 18 = 2 × 9 = [tex]2^{1}[/tex] × 3²
Then
[tex]2^{x+3}[/tex] = [tex]2^{1}[/tex]
Since bases on both sides are equal, both 2, then equate exponents
x + 3 = 1 ( subtract 3 from both sides )
x = - 2
Then
[tex]2^{-2+3}[/tex] = [tex]2^{1}[/tex]
and
[tex]3^{-2+4}[/tex] = 3²
18 = 2 × 3²
Answer:
x=-2
Step-by-step explanation:
[tex]2 {}^{x + 3} \times 3 {}^{x + 4 = 18} [/tex]
Apply the Inverse of the Product of Power Rule
If
[tex]x {}^{y} \times x {}^{z} = x {}^{y + z} [/tex]
This means that
[tex] {x}^{y + z} = {x}^{y} \times {x}^{z} [/tex]
So in order words,
[tex](2 {}^{x} \times 2 {}^{3} ) \times (3 {}^{x} \times 3 {}^{4} ) = 18[/tex]
[tex](2 {}^{x} \times 8) \times (3 {}^{x} \times 81) = 18[/tex]
Divide both sides by 31 and 8.
We get that
[tex]2 {}^{x} \times {3}^{x} = \frac{1}{36} [/tex]
[tex]6 {}^{x} = \frac{1}{36} [/tex]
Take the log of both sides.
[tex] log_{6}( \frac{1}{36} ) = x[/tex]
[tex]6 {}^{ - 2} = \frac{1}{36} [/tex]
so
[tex]x = - 2[/tex]
Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.